Construction of political identity in Poland and the of the nation in the context of Considerations Ernesto Laclau`a. Qualitative analysis = Konstruowanie tożsamości politycznej w Polsce a mit o narodzie w kontekście rozważań Ernesto Laclau`a. Analiza dyskursywna - Młyńczyk, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study of constructing a political identity in Poland can be read in the category of myth Ernesto Laclau`a nation. In Poland, there is a metaphorical use of the compounds. To the vocabulary of political language permeates the media. The Polish political debate used xenophobic and anti-Semitic expressions. Political organizations associated with the right side of the political spectrum claim the right to appropriate the concept of nation.
Keywords: nation; political identity; political discurs; populism; populistical discurs; naród; tożsamość polityczna; dyskurs polityczny; populizm; dyskurs populistyczny